Oman-Speech: A Multi-Layer Annotated Speech Corpus for Omani Arabic Dialects - Khadhuri, Rayyan S Al; Mahrouqi, Firas Al; Mandhari, Salim Al; Kathiri, Amir al-; Alshahri, Omar Said; Alsaqr, Ghassab Mansoor; Mudhsh, Badri Abdulhakim; Fatnassi, Tarek (2nd Workshop on NLP for Languages Using Arabic Script (AbjadNLP 2026), 2026)
Automatic Speech Recognition (ASR) has achieved strong performance in high-resource languages; however, Dialectal Arabic remains significantly under-resourced. This gap is particularly evident in Oman, where Arabic exhibits substantial sociolinguistic variation shaped by settlement patterns between sedentary (Hadari) and nomadic (Badu) communities, which are often overlooked by urbancentric or generalized Gulf Arabic datasets. We introduce OMAN-SPEECH, a sociolinguistically stratified spoken corpus for Omani Arabic comprising approximately 40 hours of spontaneous and semi-spontaneous speech from 32 speakers across 11 Wilayats (provinces). The corpus is balanced to capture regional and lifestyle variation and is annotated at the sentence level with Arabic transcription, English translation, and phonetic transcription using the International Phonetic Alphabet (IPA) through a human-in-the-loop annotation pipeline. OMAN-SPEECH provides a foundational resource for evaluating ASR and related speech technologies on Omani and Gulf Arabic varieties and supports more granular modeling of regional dialectal variation.
Keywords: Linguistique -- Oman

Soqotra, Mahra, and Dhofar Studies in Modern South Arabian Languages and Oral Literatures. A Volume in Honor of Vitaly Naumkin - Bulakh, Maria; Kogan, Leonid (Brill, 2025)
Keywords: Linguistique -- Oman

Language Borrowing in Oman: Evidence of Balushi Influence in Spoken Omani Dialect - Dhahab, Maryam Nawaf al- (Sultan Qaboos University, 2025)
This study explores the borrowing of Balushi words into the Omani dialect, focusing on three commonly used terms: /sˤar.da/ (severe cold), /ˈpæn.ke/ (fan or propeller) and /ˈkun.bil/ (thick blanket). Through a survey of 50 participants from eight Omani governorates, the research examines the usage, pronunciation and recognition of these words among native speakers. The study suggests that while these terms may share origins with Farsi and Hindi, their phonetic features and local pronunciations point to more direct borrowing from Balushi. The research highlights the impact of multilingualism in Oman and the subtle ways in which borrowed words become embedded in local identity. Despite the limited sample size, this paper encourages further investigation into linguistic borrowing and regional variation in Oman.
Keywords: Linguistique -- Oman

Miranda Morris, Ethnographic Texts in the Baṭḥari Language of Oman - Rubin, Aaron D. (Journal of Semitic Studies, 2025)
Keywords: Linguistique -- Oman; Recension

المسائل النحوية والصرفية في كتاب الإبانة في اللغة العربية لسلمة بن مسلم العوتبي - زيدان, انتصار محمد; قدوري, سوسن غانم (مجلة بحوث اللغة, 2025)
من اللغات التي تتميّز بنظام تركيبيٍّ نحويٍّ، وصرفيٍّ، وصوتيٍّ -فريدٍ- هي اللغة العربية، فإنها أجزل لغات العالم لفظاً، وأمكنِها مقدرةً على استيعاب المفردات، ولكلماتها وألفاظها دلالاتٌ مختلفات، ومعلومٌ أنّ اللغة فنٌّ لا يولد مع الإنسان إلا بعد المخالطة، والدراسة، وطول النظر، والعكوف على مصادرها - بحثاً وتقصّياً- للوقوف على بدائعها وأسرارها، وممن لَمَعَ نجمه، وبَانَ أُفقُه -امتداداً على طول الزمن- عالمٌ عاش في القرن الخامس الهجري عرف بـ "العوتبيّ" و"الصحاري"، إذ ترك لنا كتاباً في أربعة أجزاء أسماه: "الإبانة"، في بيان كثير من معاني اللغة، ومضمّناً إياه كثيراً من مسائل النحو والصرف والبلاغة والمعاني، جاء هذا البحث متناولاً بيانَ مكانة هذا العالم الكبير الذي غفلت عنه الدراسات، ثم بعضاً من أهم المسائل النحوية والصرفية الواردة في كتابه "الإبانة"، واستخراج هذا الكنز المتناثر بين طيّاته، وتناولها بالشرح والتفصيل ليستفيد منها الباحثون، على الرغم من ان هذا الكتاب مُعجَميٌّ؛ إلا أنّ هذه المسائل قد أخذت نصيبها منه عنده في الكتاب، جاء البحث في مبحثين: الأول تعريف بالعوتبيِّ وشيء من ترجمته، ثم تعريفاً بكتابه "الإبانة"، مع بيان محتواه وموضوعه، وأبرز ملامح منهجه فيه ، وجاء المبحث الثاني: باحثاً بعضاً من أهم المسائل النحوية والصرفية الواردة فيه، فأصحبت المسائل: أربعة نحويّات، وثلاثةٍ صرفيات، ثم خاتمة، مع أبرز النتائج.
Keywords: Linguistique -- Oman

الأمثال الشَّحْرِيَّة: ذاكرة الثقافة الشفوية في ظفار، عُمان = Shaḥrī Proverbs: the Memory of Oral Culture in Dhofar, Oman - الشحري, محمد مستهيل (Athīrat: Journal of Ancient Arabia, 2025)
ملخص البحث ‫يمكن القول بأن الأمثال الشحرية تشكّل جزءًا أساسيًا من الذاكرة الثقافية التواصلية ومن الخزان الثقافي الخاص في هذه الديار عبر التاريخ والتي تعكس بلا شك علاقة الإنسان بالأرض واستمراريته في أرض ظفار. يتناول البحث عددًا من الأمثال المنطوقة التي تعبر عن ثقافة مجتمعية تعتمد على الذاكرة في التواصل واكتساب المعرفة وتداول الثقافة. تكشف الأمثال عن المصادر الأولية في الثقافة الشعبية ومدى ارتباطها بالمعتقد الديني أو العرف الاجتماعي. وتتناول جزءا من ثقافة المجتمع تجاه المرأة فتقدر المرأة وتثمن دورها الاجتماعي، وتوضح الأمثال الشحرية عن نمط اقتصادي رعوي يشارك فيه الرجال والنساء معًا.‬
Keywords: Linguistique -- Oman

Seven texts in the Mehri of the al-Afār tribe, Habrūt - Watson, Janet C. E.; Qumairi, Saeed al-; Alaffari, Nasser Alawadhi; Mahri, Abdullah Musallam al- (Der Perlentaucher: Festschrift für Stefan Weninger zu seinem 65. Geburtstag am 6. August 2024, 2024)
Keywords: Linguistique -- Oman

Analysis of Tense System in Jibbali (Shehri) Language - Alkathiri, Amir Azad Adli; Mudhsh, Badri Abdulhakim (Pakistan Journal of Life and Social Sciences (PJLSS), 2024)
Keywords: Linguistique -- Oman

نحو تصنيف جغرافي جديد للمجموعات اللهجيّة في سلطنة عُمان - الكثيري, عامر (مجلة الآداب, 2024)
تسعى هذه الدراسة إلى تقديم تصنيف جغرافي جديد للمجموعات اللهجية في سلطنة عمان انطلاقا من التصنيف الذي وضعه كلايف هولز (Clive Holes) للمجموعات اللهجية في شمال سلطنة عمان ووسطها في مقالته المنشورة عام 1989، التي حددها - بناء على الوحدات اللغوية الصوتية والصرفية- في أربع مجموعات لهجية: مجموعتين بدويتين ومجموعتين حضريتين. وتروم الدراسة الحالية متابعة عدد من الوحدات اللغوية التي وظّفها كلايف هولز في النطاق الجغرافي المحدد عنده بـ 15 موقعا جغرافيا؛ بغية مقارنة أوجه الاتفاق والاختلاف بين الدراسة الحالية ودراسة هولز، فضلا عن ذلك فإن الدراسة تسعى إلى رصد الصور المنطوقة لهذه الوحدات اللغوية في نطاق جغرافي أوسع من النطاق الذي حدّده هولز، يشمل المجموعات اللهجية في محافظتي ظفار ومسندم، التي استبعدها كلايف هولز من دراسته. وقد جُمعت المادة اللغوية لهذه الدراسة من زيارات ميدانية قام بها الباحث بين عامي 2018 و2019 إلى مختلف محافظات سلطنة عمان. وخلصت الدراسة بناء على الوحدات اللغوية المدروسة إلى أن بعض ما أورده هولز على أنه مجموعة لهجية واحدة يمكن أن يدرج في مجموعتين لهجيتين أو أكثر، إذ إن مجموعة (بدو1) عند هولز تضعها الدراسة الحالية في ثلاث مجموعات لهجية، هي: المجموعة البدوية في محافظة البريمي، والمجموعة البدوية في محافظة شمال الباطنة، والمجموعة البدوية في محافظة جنوب الشرقية. وتضيف الدراسة أيضا مجموعة لهجية جديدة في النطاق الجغرافي الحضري الذي حدده هولز، هي: المجموعة الحضرية في محافظة الظاهرة والمناطق الجبلية المتصلة بها في ولاية الخابورة بمحافظة شمال الباطنة، وتضيف الدراسة كذلك مجموعات لهجية في المناطق التي استبعدها هولز، مثل: المجموعة الحضرية في محافظة مسندم، والمجموعين الحضرية والبدوية في محافظة ظفار. ولعلّ مردّ بعض هذه الاختلافات راجع إلى التطورات الصوتية والصرفية التي حدثت خلال المدة الزمنية بين دراسة هولز والدراسة الحالية.
Keywords: Linguistique -- Oman

Quadriliterals and “quinqueliterals” in Omani Mehri - Bendjaballah, Sabrina; Ségéral, Philippe (South Arabia: Old Issues, New Perspectives: Proceedings of the Workshop at the University of Erlangen-Nürnberg on December 19, 2019, 2022)
Keywords: Linguistique -- Oman

Demonstratives in Musandam Arabic: Distinctive Archaisms and Innovations - Anonby, Erik; Bettega, Simone; Procházka, Stephan (Arabica, 2022)
Abstract This study introduces and analyzes proximal and distal singular demonstratives in fourteen varieties of Musandam Arabic, a little-documented dialect group located on Musandam Peninsula in northern Oman and neighbouring areas of the United Arab Emirates. Following an overview of the dialect group in its regional context, the study provides a description of singular demonstratives from the point of view of phono-logy, morphology, and geographical distribution. The study then focuses on two salient features found in several of the varieties under investigation: gender distinction based on consonantal alternation ( d -based masculine forms vs t -based feminine forms); and gemination of the feminine t -element. While the former is attested, albeit rarely, in other Arabic dialects, the latter is unheard of. In the last section of the article, some hypotheses are put forward as to how these forms could have developed from a historical point of view, in light of data from different Arabic and Semitic varieties. While the gemination of the t -element is best regarded as a Musandam-internal innovation, the d : t consonantal alternation reinforces the putative historical link between south-western Arabia and Oman.
Keywords: Linguistique -- Oman

Dialect Variation among Omani Migrants in Muscat: The Construction of Social Identity through Style Shifting - Ambu-Saidi, Suaad (Language and Identity in the Arab World, 2022)
Keywords: Linguistique -- Oman

A Text in the Jibbali/Shehret Dialect of al-Ḥallānīya (Kuria Muria) with a Grammatical Commentary - Castagna, Giuliano (Semitic Dialects and Dialectology Fieldwork—Community—Change, 2022)
Keywords: Linguistique -- Oman

Tǝghamk Āfyǝt: A Course in Mehri of Dhofar - Watson, Janet C. E. (Semitica viva, 2020)
This book is the first coursebook to deal with the Modern South Arabian language, Mehri. Focussing on Mehri as spoken in Central Dhofar, Oman, the work results from several years' close collaboration with four native speakers of Mehri. The book is multimodal, supported by a large number of audio and audio-visual texts from the Mehri archive housed at the Endangered Languages Archive (ELAR) at the School of Oriental and African Studies, London. It comprises twenty lessons and a glossary of all terms occurring in the lessons. Dialogues within the lessons focus as far as possible on aspects of the traditional culture of the Mahrah, thus introducing the student not only to the language, but also to issues of cultural importance.
Keywords: Linguistique -- Oman

Functions and Uses of Active and Passive Participial Forms in Al-'Awābī District Vernacular of Northern Oman - Morano, Roberta (Al-ʿArabiyya: Journal of the American Association of Teachers of Arabic, 2020)
This article investigates the use and functions of the active and passive participial forms in the Omani vernacular spoken in al-'Awābī district, in al-Bāṭina region of northern Oman. This dialect was first described by Carl Reinhardt in 1894. No sections of his work, however, deal with the analysis of functions of participial forms in the dialect, although they are common in his texts. The data presented in this article aim to show the uses of the active participle in the everyday speech of my participants living in al-'Awābī district and the different syntactic and semantic functions it conveys. The syntactic functions of the participle in Arabic linguistics has long been debated since it is neither completely a verbal form nor a nominal. This article fits into this discussion as it brings new data and analysis of active and passive participles in Arabic dialectology with regard to the Omani vernacular spoken in al-'Awābī district.
Keywords: Linguistique -- Oman

Ruʾūs al-Jibāl Arabic in Context: A Proposal for an Expanded Typology of Southeastern Arabian Dialects - Shockley, Mark Daniel (Journal of Semitic Studies, 2023)
This paper seeks to clearly outline the features that distinguish Ruʾūs al-Jibāl Arabic (also called Šiḥḥī Arabic, Musandam Arabic) spoken on the Omani peninsula from surrounding dialects. Comparison with nearby Arabic varieties yields a few areal features (in segmental phonology) that establish a dialect continuum from the coasts of northern Oman to Musandam. A large number of phonological similarities between Ruʾūs al-Jibāl Arabic and Dhofari Arabic are then documented here for the first time. This robust but discontinuous link re-frames many of the peculiarities of Ruʾūs al-Jibāl Arabic as vestiges of a coastal southern Arabian dialect group. This finding fits a wellknown ancient pattern of northward population movements out of south Arabia, and allows for a more effective delineation of innovations unique to Ruʾūs al-Jibāl . It also offers a direction forward for an expanded framework for the classification of the Arabic dialects of southeastern Arabia, incorporating Oman's peripheries at Dhofar and Musandam.
Keywords: Linguistique -- Oman